A review on exploratory based learning implementation by integrating technology strategy in teaching and learning - Bahrudin, I. A.; Alias, M. (Hampstead Psychological Associates, 2020)
As an educator, no matter how much experience we have, there are always challenges to face in the classroom. Today, how people learn and practice something that they learn in everyday life is rapidly shifting. The integration of technology strategy in teaching and learning enable student to explore environments, reality and virtual experiences. One of learning strategy that support this notion of learning is exploratory based learning (EBL). This study examines the implementation of EBL in education concerning to its definition and technology integration. Based on the literature reviewed, EBL learning model extends from the Kolb model of learning but it takes place in a cyclical mode following four steps; concrete, experience, observation and reflection, forming abstract concepts and testing in new situations. Technology integration in EBL that focusing on learning practices are identified to be applicable in order to improve learning experiences among students in Malaysia.